2021
DOI: 10.1016/j.arthro.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative and Operative Soft-Tissue and Cartilage Regeneration and Orthopaedic Biologics of the Knee: An Orthoregeneration Network (ON) Foundation Review

Abstract: Orthoregeneration is defined as a solution for orthopedic conditions that harnesses the benefits of biology to improve healing, reduce pain, improve function, and optimally, provide an environment for tissue regeneration. Options include: drugs, surgical intervention, scaffolds, biologics as a product of cells, and physical and electro-magnetic stimuli. The goal of regenerative medicine is to enhance the healing of tissue after musculoskeletal injuries as both isolated treatment and adjunct to surgical managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…The meniscus joint capsule area has an abundant blood supply and strong healing ability and can be sutured and repaired. Liu et al reported that only fresh wound treatment could achieve a good curative effect for stable meniscus synovial tears [22]. However, many studies have shown that medial meniscus instability and wear with medial femoral condyle cartilage reduce the possibility of spontaneous healing and lead to meniscus and cartilage damage progression [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The meniscus joint capsule area has an abundant blood supply and strong healing ability and can be sutured and repaired. Liu et al reported that only fresh wound treatment could achieve a good curative effect for stable meniscus synovial tears [22]. However, many studies have shown that medial meniscus instability and wear with medial femoral condyle cartilage reduce the possibility of spontaneous healing and lead to meniscus and cartilage damage progression [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, picking the right cells for the job may also be critical as MSC from different sources can exhibit different properties even though they can have a similar phenotype, as discussed in [ 123 , 124 ]. Thus, the right cells in the right environment at the right time are needed are discussed in [ 202 , 203 , 204 ], and there is likely a need for a more “precision medicine” approach as “one size does not fit all” [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olivier did not find a significantly higher cell yield with the multiple-site technique than with the single-site technique, but only 6 patients were included 13 . Inconsistent results regarding the clinical outcome in stem cell publications in general and differences in cell count between the different studies may be explained by the heterogeneity of bone marrow harvesting techniques 26 . Recent publications demand precise guidelines for the techniques used 4 , 11 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent results regarding the clinical outcome in stem cell publications in general and differences in cell count between the different studies may be explained by the heterogeneity of bone marrow harvesting techniques 26 . Recent publications demand precise guidelines for the techniques used 4 , 11 , 26 , 27 . However, little is known about how to do this correctly.…”
Section: Introductionmentioning
confidence: 99%